CAUSES OF MISBEHAVIOURS AT JUNIOR HIGH SCHOOL IN AN EFL CLASSROOM: A CASE STUDY IN NORTH BALI - Wati, Ni Nengah Ade Indria; Suwastini, Ni Komang Arie; Wasistha, I Gusti Agung Prajna (International Journal of Language and Literature, 2019)
Misbehavior becomes a vital issue in classroom management in any classes. Aiming to analyze the causes of the seventh-grade students' misbehavior at a Junior High School in North Bali, there were 35 students of 7.6 class as the subject in this study. This class was purposefully chosen because it is the class with the highest number of misbehavior in grade 7. The data were mainly collected through interviews, while secondary data were collected through observation to crosscheck the validity of the students' answers. This study shows that there were five causes of misbehavior: boredom, sleepiness, lack of motivation from the teacher, poor quality of teaching, and lack of preparation from the students. It implies that teachers need to guide the students to adapt to the new learning environment and modify their teaching style to get students' attention during classroom time.